UJI POTENSI EKSTRAK DAUN SALAM (Syzygium polyanthum) SEBAGAI ANTIHIPERGLIKEMIA PADA MENCIT (Mus musculus) YANG DIINDUKSI GLUKOSA - Derra Ashara Mahardhika; Vidya Kartikaningrum; Andita Wijayanti (Biospektrum Jurnal Biologi, 2023)
Hyperglycemia is a state of increasing blood sugar levels above the limits normal. Hyperglycemia occurs because of an increase in glucose levels in the blood that is more than 126 mg/dl for a fasting state. Bay leaves are used as a treatment for hyperglycemia. The content that exists in bay leaf such as alkaloids and saponins which can increase insulin secretion from beta cells pancreas. The purpose of this study was to determine the effectiveness of bay leaf extract (Syzygium polyanthum) as antihyperglycemic in mice glucose induced. This study was used an experimental method with a pretest posttest control group design with divided mice test animals into 5 groups: the negative control was given 0.5% CMC Na, the positive control was given glibenclamide at a dose of 0.65 mg/kgBW, the treatment group was given extract bay leaf ethanol at a dose of 125 mg/kg, a dose of 250 mg/kg and a dose of 500 mg/kg. The mice were fasted for 12 hours while still being given water and then measured fasting blood glucose levels using a glucometer then the mice were induced with 20% glucose so that the mice experienced hyperglycemia (˃126 mg/dl). The results showed that the ethanol extract of bay leaves was effective in reducing blood glucose levels in hyperglycemic with mice decrease in the average extract dose of 125 mg/kgBW of 79 ± 8.31 mg/dl, dose of 250 mg/kgBW of 79.4 ± 6, 82 mg/dl, and a dose of 500 mg/kgBW of 87.4 ± 9.66 mg/dl. Keywords: Bay leaf (Syzygium polyanthum), Mice, Hyperglycemia, Glucose.